A Caribbean mystery - Christie, Agatha, 1890-1976. (New York : Signet, 2000)
Miss Marple, on holiday on the island of St. Honore, is drawn into the investigation of the death of Major Palgrave, a man found murdered shortly after regaling her with boring stories of a murderer he once knew.
"A Miss Marple mystery"--Cover.
Young Adult
Keywords: Marple, Jane (Fictitious character) -- Fiction; Murder -- Fiction; Women detectives -- England -- Fiction; Homicide -- Fiction; Marple, Jane (Fictional character) -- Fiction; Mystery fiction; Women detectives -- Fiction; West Indies -- Fiction; West Indies -- Fiction